Production of spherulitic iron with high stretch ratio values in the cast condition - E. I. Marukovich; S. G. Molev (Литьë и металлургия)
The article presents the possibility of obtaining high values of spherulitic iron stretch ratio in the cast condition at treatment of high-sulfur cast irons.